New Therapies of Liver Diseases - Toniutto, Pierluigi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this Special Issue of the journal, advancements in the treatment of liver diseases are illustrated by international experts in the field. New treatment options for primary biliary cirrhosis and, hopefully, primary sclerosing cholangitis are discussed. Up-to-date pharmacological therapy for preventing liver cirrhosis decompensation and treating acute-on-chronic liver failure is highlighted. Furthermore, new treatments for cholangiocarcinoma, based on biological and tissue markers, will be available in the near future, aiming to surpass the current unsatisfactory results of traditional therapies. Immunotherapy has been applied to hepatocellular carcinoma (HCC). The new first-line treatment, combining atezolizumab plus bevacizumab for HCC in the intermediate and advanced stages, will allow for an increase in patient survival in the near future. Liver transplantation (LT) remains the preferred treatment for many patients with end-stage liver diseases and HCC. The selection criteria for LT in patients with HCC moved from morphological to dynamic criteria, such as those derived from the assessment of tumor responses to locoregional and/or systemic treatments before transplantation. This allowed many patients who would have been excluded from a transplantation with the old selection criteria to access one. Finally, a very interesting issue regarding new indications for liver transplantation is illustrated.